2015
DOI: 10.5897/ajbm2015.7797
|View full text |Cite
|
Sign up to set email alerts
|

The effect of board size and composition on the financial performance of banks in Nigeria

Abstract: This paper analyzed the effects of board size and board composition on the performance of Nigerian banks. The financial statements of five banks were used as a sample for the period of nine years and the data collected were analysed using the multivariate regression analysis. The paper found that board size has significant negative impact on the performance of banks in Nigeria. This signifies that an increase in Board size would lead to a decrease in ROE and ROA. On the other hand, board composition has a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Bebeji et al (2015) assessed the extent to which board size and composition influence the performance of listed banks in Nigeria. The researchers adopted a multivariate regression analysis technique on five banks for a span of nine years.…”
mentioning
confidence: 99%
“…Bebeji et al (2015) assessed the extent to which board size and composition influence the performance of listed banks in Nigeria. The researchers adopted a multivariate regression analysis technique on five banks for a span of nine years.…”
mentioning
confidence: 99%
“…In previous study of Bebeji et al (2015), board size and board composition have been proven to be related to the performance of bank in Nigeria. They suggested that board size is inversely related while board composition is positively associated to bank performance.…”
Section: Journal Of Public Administration and Governancementioning
confidence: 96%
“…Some past studies using Tobin"s Q (Al-Saidi and Al-Shammari, 2013; Belhaj and Mateus, 2016) as their measurement of bank performance. In contrast, other researchers using ROA and ROE (Tomar and Bino, 2012;Fanta et al, 2013;Bebeji et al, 2015;Boussaada and Karmani, 2015;Liang et al, 2013;Pathan, Skully, and Wickramanayake, 2007;Sheikh and Karim, 2015) as the bank performance measures.…”
Section: Journal Of Public Administration and Governancementioning
confidence: 98%
See 1 more Smart Citation
“…The study by Ojong and Ekponta (2014), which discusses the role of IA in the efficiency of financial performance in Nigerian higher education institutions, revealed that the role of IA in improving financial performance is not very significant, and the reason is the absence of employees' independence from senior management. The existence of internal entirely independent auditors has a positive impact on the financial performance of banks (Aminu et al, 2015). The contribution of the audit to improving the financial performance of banks is related to several things, including the presence of experienced and competent auditors, the auditors obtaining sufficient rights for them, and the extent of the contribution of the institutions' management to overcom-ing the difficulties (Tapang & Ibiam, 2019).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%